2014
DOI: 10.3109/13880209.2014.948633
|View full text |Cite
|
Sign up to set email alerts
|

Two antigenotoxic chalcone glycosides fromMentha longifoliasubsp.longifolia

Abstract: Context: Mentha L. (Labiatae) species (mint) with their flavoring properties have been used in food industries for centuries. Besides they have a great importance in drug development and medicinal applications due to various bioactive compounds of several members of the genus. Objective: The aim of this study was to isolate bioactive compounds with antimutagenic potential by bio-guided fractionation and determine their structures by spectroscopic methods. Materials and methods: The structural elucidation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The UV spectra of 1 and 2 exhibited two absorbance bands at around 250 and 355 nm. The MS spectrum of 1 showed a protonated molecular ion [M+H] + at 447 m/z and a fragment ion at 269 m/z , which were in agreement with the reported value . Therefore, compound 1 was identified as apigenin‐7‐ O ‐glucuronide .…”
Section: Resultssupporting
confidence: 87%
“…The UV spectra of 1 and 2 exhibited two absorbance bands at around 250 and 355 nm. The MS spectrum of 1 showed a protonated molecular ion [M+H] + at 447 m/z and a fragment ion at 269 m/z , which were in agreement with the reported value . Therefore, compound 1 was identified as apigenin‐7‐ O ‐glucuronide .…”
Section: Resultssupporting
confidence: 87%
“…In the Ames test, reversion to histidine prototrophy occurs because of mutations that restore gene function and allow the cells to synthesize histidine [30,35]. In this study, the chalcones 4-CL and DMF did not show mutagenicity.…”
Section: Discussionmentioning
confidence: 53%
“…Mutagenicity was measured using the mutagenic index (MI), which was calculated for each concentration. MI = (number of revertant colonies per plate in the test per plate)/(number of revertant colonies per plate in the negative control), and a compound is considered mutagenic when MI ≥ 2 [35]. For the antimutagenicity assays was calculated the mutagenicity variation (MV), in percentage, using the formula MV = {[(S1-So) / (M-S0)] -1 } × 100.…”
Section: Experimental Procedures and Analysismentioning
confidence: 99%
“…Peak 21 was detected at m/z 447 in both extracts and produced fragment at m/z 285 [M-H-hexose] -. This compound is assigned to be luteolin 7-O-glucoside, by comparing the mass fragmentation and Rt of standard, which previously isolated from M. pulegium (Taamalli et al, 2015) and M. longifolia (Orhan et al, 2012;Guvenalp et al, 2015).…”
Section: Lc-esi-ms Analysismentioning
confidence: 99%
“…The phytochemical constituents reported from M. longifolia and M. pulegium are flavonoids (Sharaf et al, 1999;Guvenalp et al, 2015;Taamalli et al, 2015), phenolic acids (Guvenalp et al, 2015;Taamalli et al, 2015), essential oils (El-Ghorab, 2006), dihydrochalcone glycosides (Guvenalp et al, 2015) and β-sitosterol glycosides (Ali et al, 2002). Flavonoids are the major reported metabolites, they occurred mostly as flavones and their glycosides (Baris et al, 2011;Orhan et al, 2012;Gulluce et al, 2013;Guvenalp et al, 2015;Taamalli et al, 2015), while C-glycosyl flavones (Sharaf et al, 1999), methoxyflavone aglycones (Zaidi et al, 1997;Taamalli et al, 2015), flavanones and their glycosides (Krzyzanowska et al, 2011;Taamalli et al, 2015), and flavonol glycosides (Akroum et al, 2009) were also reported.…”
Section: Introductionmentioning
confidence: 99%